Collagen I-based scaffolds negatively impact fracture healing in a mouse-osteotomy-model although used routinely in research and clinical application. (1st March 2019) - Lang, Annemarie; Kirchner, Marieluise; Stefanowski, Jonathan; Durst, Mattea; Weber, Marie-Christin; Pfeiffenberger, Moritz; Damerau, Alexandra; Hauser, Anja E.; Hoff, Paula; Duda, Georg N.; Buttgereit, Frank; Schmidt-Bleek, Katharina; et al.
Graphical abstract: Abstract: Although several biomaterials for bone regeneration have been developed in the last decades, clinical application of bone morphogenetic protein 2 is clinically only approved when applied on an absorbable bovine collagen I scaffold (ACS) (Helistat; ACS-H). In research, another ACS, namely Lyostypt (ACS-L) is frequently used as a scaffold in bone-linked studies. Nevertheless, until today, the influence of ACS alone on bone healing remains unknown. Unexpectedly, in vitro studies using ASC-H revealed a suppression of osteogenic differentiation and a significant reduction of cell vitality when compared to ASC-L. In mice, we observed a significant delay in bone healing when applying ACS-L in the fracture gap during femoral osteotomy. The results of our study show for the first time a negative influence of both ACS-H and ACS-L on bone formation demonstrating a substantial need for more sophisticated delivery systems for local stimulation of bone healing in both clinical application and research. Statement of Significance: Our study provides evidence-based justification to promote the development and approval of more suitable and sophisticated delivery systems in bone healing research. Additionally, we stimulate researchers of the field to consider that the application of those scaffolds as a delivery system for new substances represents a delayed healing approach rather than a normal bone healing which could greatly impact the outcome of those studies and play a pivotal role in the translation to the clinics. Moreover, we provide impulses on underlying mechanism involving the roles of small-leucine rich proteoglycans (SLRP) for further detailed investigations.